Minority Police Officers in Law Enforcement: The Intersection of Identity and Experience - Mendes, Yanick (Applied Dispute Resolution Journal, 2025)
This paper investigates the relationship between the identities of minority police officers and their professional experiences, focusing on the interplay between identity, societal interactions, and individual life experiences. The study builds upon the premise that identity significantly influences both personal and professional dynamics, shaping how individuals navigate their roles within society. Historical events, including the Stonewall Riots of 1969, the Rodney King Riots of 1992, and the killing of George Floyd in 2020, serve as pivotal moments that have profoundly affected the relationship between law enforcement and minority communities. These events contextualize the broader societal tensions and the complexities that minority officers face within their roles. As a police officer with four years of experience, the author reflects on how race and sexuality have both positively and negatively influenced their career. The study examines whether these effects lean more toward the positive or the negative and to what extent. Furthermore, this study aims to shed light on the decreased retention rates of minority police officers and their direct correlation to community-police relations. Given the underrepresentation of certain identities in our sample, the findings may not be generalizable to all minority groups in law enforcement. By exploring these dynamics, this research contributes valuable insights into enhancing understanding and improving connections between law enforcement and marginalized communities.